2004
DOI: 10.1038/ni1059
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Toll-like receptor signals are required for reversal of regulatory T cell–mediated CD8 tolerance

Abstract: One chief barrier to cancer immunotherapy is tumor-specific T cell tolerance. Here we compared the ability of hemagglutinin (HA)-encoding recombinant viruses versus 'HA-loaded' dendritic cells to reverse HA-specific CD8 tolerance and to protect mice from tumor challenge. Both vaccines were comparable in activating naive HA-specific CD8(+) T cells. However, in circumstances of established tolerance, viral vaccines could break CD8 tolerance in the presence of CD4(+)CD25(+) regulatory T cells, whereas dendritic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
311
2
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(332 citation statements)
references
References 43 publications
15
311
2
3
Order By: Relevance
“…Further, sustained adjuvant delivery (mediated in basic immunological studies by repeated injections) have been shown to help break tolerance to tumor antigens in the setting of cancer vaccines, and so the ability to release adjuvant molecules for a period of several days could be a second important opportunity for LbL vaccine films. 62 To regulate the release of antigen and adjuvant in composite films containing ova and CpG, we explored different sequences of layering in order to determine the impact of film architecture on the loading and release kinetics for the two components. We were also interested in examining potential interactions between ova and CpG within the film structure.…”
Section: Resultsmentioning
confidence: 99%
“…Further, sustained adjuvant delivery (mediated in basic immunological studies by repeated injections) have been shown to help break tolerance to tumor antigens in the setting of cancer vaccines, and so the ability to release adjuvant molecules for a period of several days could be a second important opportunity for LbL vaccine films. 62 To regulate the release of antigen and adjuvant in composite films containing ova and CpG, we explored different sequences of layering in order to determine the impact of film architecture on the loading and release kinetics for the two components. We were also interested in examining potential interactions between ova and CpG within the film structure.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, CD4 + CD25 + regulatory T cells and myeloid suppressor cells can be recruited to the tumor site, where they mediate tolerance against tumor antigens and dampen tumoricidal responses [37]. Studies have demonstrated that tolerance against tumor antigens can be overcome through activation of TLR signaling by viral vectors, which may explain the efficacy of VRP-DCs [15]. However, while VRP-DCs can inhibit the growth of established tumors in FVB/N mice, preliminary studies have failed to demonstrate tumor regression in transgenic mice tolerant to the neu antigen (T. Moran, R. Johnston, and J. Serody, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…Viral vectors can efficiently deliver tumor antigens to DCs in the context of an immunostimulatory viral infection, resulting in optimal DC activation [11][12][13][14]. Moreover, viral vectors may provide the persistent TLR stimulation deemed necessary for overcoming T reg -mediated suppression and thus breaking tolerance against tumor antigens [15]. We previously found that Venezuelan equine encephalitis virus replicon particles (VRP) could efficiently transduce human DCs, resulting in maturation and secretion of proinflammatory cytokines [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a prime-boost schedule in which three priming vaccinations were administered with only three days between vaccinations followed by a boost vaccination fifteen days later elicited larger TRP-2 180−188 -specific CD8 + T cell responses than a schedule in which identical vaccines were administered on a weekly schedule ( Figure 1D). The short time interval between priming vaccinations might supply sustained toll-like-ligand receptor signaling, allowing vaccines to break tolerance and elicit large CD8 + T cell responses [30].…”
Section: Discussionmentioning
confidence: 99%